Population Mobility and Transboundary Environmental Problems - Michael Hoel; Perry Shapiro (Center for Economic Studies and ifo Institute (CESifo), 2001)
A standard result in the literature on environmental economics is that efficient environmental policies regulating transboundary pollution will be adopted only if there is interjurisdictional coordination. Efficient policies can be adopted as a result of interregional treaties or mandated by a central authority. The present paper demonstrates that if there is perfect population mobility between the regions affected by the transboundary pollution, the efficient outcome is a Nash equilibrium of the policy game between regional authorities. This is true independently of what policies are available to the regional authorities. However, there may be more than one Nash equilibrium, so that policy coordination may be necessary in order to achieve the best equilibrium.
Keywords: 330; Transboundary pollution; population mobility; federalism